A Scheduling Framework for Railway Container Terminals Based on Internet of Vehicles. Issue 5 (March 2019) - Li, Siqiao; Wang, Li
Abstract: In this paper, we establish a dynamic optimization model based on the information of container trucks collected by internet of vehicles (IOV). This research aims to realize the direct loading and unloading operation between the container trucks and the container trains to reduce waiting time of the container trucks. Finally, the frame we introduced can get an optimal job sequence and is helpful for the operation in railway container terminals.